2013
DOI: 10.1007/s00270-013-0571-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Assessment After Palliative Interventions to Manage Malignant Ureteral Obstruction

Abstract: Purpose Malignancies may cause urinary tract obstruction, which is often relieved with placement of a percutaneous nephrostomy tube, an internal double J nephro-ureteric stent (double J), or an internal external nephroureteral stent (NUS). We evaluated the affect of these palliative interventions on quality of life (QoL) using previously validated surveys. Methods Forty-six patients with malignancy related ureteral obstruction received nephrostomy tubes (n = 16), double J stents (n = 15), or NUS (n = 15) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 24 publications
1
35
0
4
Order By: Relevance
“…The discussion concerning PNT versus JJ stents is ongoing. A recent study measuring quality of life three times, after a PNT, JJ stent or internal-external nephroureteral stent placement, showed no significant differences, but the group with a PNT required more frequent tube changes [18]. The present patients described tube changesscheduled or acutelyas a feared situation owing to discomfort, pain and insecurity.…”
Section: Clinical Considerationsmentioning
confidence: 66%
“…The discussion concerning PNT versus JJ stents is ongoing. A recent study measuring quality of life three times, after a PNT, JJ stent or internal-external nephroureteral stent placement, showed no significant differences, but the group with a PNT required more frequent tube changes [18]. The present patients described tube changesscheduled or acutelyas a feared situation owing to discomfort, pain and insecurity.…”
Section: Clinical Considerationsmentioning
confidence: 66%
“…The purpose of this study was to examine the impact of ureteral obstruction, urinary stent or diversion procedures, and the aftermath of the foregoing on quality of life-as voiced directly by patients. Findings were unexpected, particularly in view of previous studies that have not consistently captured major, questionnaire-derived, negative quality of life findings [3][4][5]. We observed that over two-thirds of the patients we interviewed described the aftermath of a urinary stenting or diverting procedure as highly symptom-laden.…”
Section: Discussionmentioning
confidence: 61%
“…The finding of ureteral obstruction due to malignancy carries a poor prognosis with a resulting median survival of 3 to 7 months, and confers a worse overall prognosis [4,6]. Relief of obstruction is usually achieved by placement of a percutaneous nephrostomy tube, an internalized double J nephroureteral stent, or an internal/external nephroureteral stent (NUS) [7]. Our patient had rejected suggested bilateral percutaneous nephrostomy as modality of decompression and accepted life saving dialysis.…”
Section: Dear Sirmentioning
confidence: 88%